Polystyrene nanoplastics induced cardiomyocyte apoptosis and myocardial inflammation in carp by promoting ROS production. Issue 125 (June 2022) - Wu, Hao; Guo, Jinming; Yao, Yujie; Xu, Shiwen
Abstract: Nanoplastics (NPs) existing in aquatic ecosystem is an emerging environmental pollutant, which has become a nagging serious environmental problem. Miniaturized plastic fragments with different diameters have different penetration capabilities to body tissues, and thus may have different toxicity to the target organs. However, the specific toxicological effects and mechanisms of NPs with different particle sizes on aquatic animal hearts are still unknown. To this end, carps were directly exposed to the aqueous environment of polystyrene NPs (1000 μg/L, PS-NPs) with three particle sizes (50 nm, 100 nm and 400 nm), respectively, for 28 days. H&E and TUNEL staining displayed that exposed to PS-NPs of three diameters all caused myocardial tissue inflammation and cardiomyocyte apoptosis in carps. Of note, at the same exposure concentration, the damage caused by PS-NPs with particle size of 50 nm was more serious than that of 100 nm and 400 nm. Further research found that, in carp hearts exposed to PS-NPs, the levels of carp innate immunity-related components TLR4 and NOX2 were significantly higher than those in controls and were negatively correlated with the exposed particle size. The content of ROS increased significantly, the activities of antioxidant enzymes (CAT, SOD1 and Gpx1) decreased, and MDA accumulated. In addition, as the particle size of PS-NPs decreased, Th1 cells gradually replaced Th2 cells to dominate, the Th1/Th2 balance was dysregulated, and the expression of apoptosis-inducing pathway IGFBP3/p53/ACHE-related genes was increased, markedly. Overall, our study results demonstrated that PS-NPs exposure caused oxidative stress, resulting in inflammation and apoptosis in carp heart, and the degree of damage was negatively correlated with the particle size of PS-NPs. Our work enriched the theoretical basis for NPs toxicological research and shed new light on the risk of NPs exposure. Graphical abstract: Image 1 Highlights: PS-NPs exposure induced oxidative stress by triggering TLR4/NOX2 signal axis. PS-NPs exposure caused Th1/Th2 imbalance mediated inflammation. PS-NPs exposure activated IGFBP3/p53/ACHE signaling pathway to induce apoptosis. The adverse effects of small-sized PS-NPs particles were higher than those of large-sized particles.